Spoiling for a Fight: B Lymphocytes As Initiator and Effector Populations within Tertiary Lymphoid Organs in Autoimmunity and Transplantation - Alsughayyir, Jawaher; Pettigrew, Gavin J.; Motallebzadeh, Reza (Frontiers in Immunology, 2017)
Tertiary lymphoid organs (TLOs) develop at ectopic sites within chronically-inflamed tissues, such as in autoimmunity and rejecting organ allografts. TLOs differ structurally from canonical secondary lymphoid organs (SLOs), in that they lack a mantle zone and are not encapsulated, suggesting that they may provide unique immune function. A notable feature of TLOs are the frequent presence of structures typical of germinal centres (GC). However, little is known about the role of such GCs, and in particular, it is not clear if the B cell response within is autonomous, or whether it synergises with concurrent responses in SLOs. This review will discuss ectopic lymphoneogenesis and the role of the B cell in TLO formation and subsequent effector output in the context of autoimmunity and transplantation, with particular focus on the contribution of ectopic GCs to affinity maturation in humoral immune responses and to the potential breakdown of self-tolerance and development of humoral autoimmunity.